Psychological Flow of Post-Graduate Students at Tishreen University (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The purpose of this study was to determine the level of Psychological Flow among post-graduate students at Tishreen University, as well as the differences in their Psychological Flow according to the variables: gender, academic level, and academic specialization.The  study's sample was selected by a proportional stratified random method, and the number of sample members was (424) students: (360) students in the master degree, and (64) students in the doctoral.To achieve the aim of the study, the researcher used the descriptive research methodology, and the measure of psychological flow (prepared) which consists of (24) items.The study showed this results: Most of post-graduate students have an average level of psychological flow, (73%) of their total. There are no statistical significant differences in psychological flow among the sample members according to gender. while there were statistical significant differences in psychological flow among the sample members according to academic level in favor of doctoral students. Also there were statistical significant differences in psychological flow among the sample members according to academic specialization in favor of scientific colleges students.